Model of Batak Toba Values and Perceived Organizational Support on The Psychological Well-Being of Batak Toba Civil Servants in North Sumatera - Nenny Ika Putri Simarmata (Universitas Ahmad Dahlan, 2024)
The Batak ethnic group is ranked as the third-largest ethnic group in Indonesia after the Javanese and Sundanese ethnic groups. As one of the ethnic groups that still strongly uphold their traditions, the Batak ethnic group experiences many conflicts within their community. This becomes a stress trigger for individuals of the Batak ethnic group if they are unable to meet the demands of their traditions, which can ultimately threaten their well-being. This research aims to develop a model of the influence of Batak values and perceived organizational support on the psychological well-being of Batak civil servants in North Sumatera. This research uses an explanatory survey method with descriptive and verificative analysis. Based on disproportionate sampling techniques, the study was conducted on 636 civil servants in five regencies and cities in North Sumatera. The model testing uses Structural Equation Modeling (SEM) based on component/variance, specifically the Partial Least Square (PLS) technique, with the SmartPLS software. The results of the study indicate that the Batak values, which are used as a guide in the lives of Batak civil servants, and their positive perceptions of the institutions where they work, simultaneously influence the psychological well-being of Batak civil servants. The variables Hamoraon, Hagabeon, Hasangapon, and perceived organizational support collectively contribute 41% to the psychological well-being of Batak civil servants in North Sumatera. Therefore, the position of Batak values and perceived organizational support is very important, as these two variables have a significant impact on the psychological well-being of Batak Toba civil servants in North Sumatera.